2005
DOI: 10.1088/0741-3335/47/5a/016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma based waste treatment and energy production

Abstract: During the past centuries, industrial processes and energy conversion plants have shown no or little care for environmental quality. The result is a huge accumulation of pollution and hazardous by-products, left as a heritage for the present and future generations. Recuperation of by-products or thermal energy is not only motivated by cost saving, but also by resource saving considerations. Environmental awareness is more than staying within the lines of the existing regulations.By the application of a plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 5 publications
0
48
0
1
Order By: Relevance
“…RF or MW plasmas don't have electrode erosion but have low energy efficiency, about 40 % to 70 % (60 % to 90 % for arc torches) [73]. From this review, it clearly appears that the main plasma torch technology applied to waste gasification is the DC technology which is used in all the studies excepted in [32,85,90] In [66], one can notice that the H 2 and CO yields are strongly linked to the original composition of the waste treated and can vary, with the same experimental conditions, from 49.4 vol% to 64.4 vol% for H 2 and from 24.8 vol% to 36 vol% for CO in function of the nature of the waste. It is important to keep in mind that the H 2 and CO rates in the crude syngas is strongly linked to the oxidizing agent injected and/or the moisture content in the waste treated.…”
Section: Waste Gasification By Plasma Process At Lab Scalementioning
confidence: 97%
See 3 more Smart Citations
“…RF or MW plasmas don't have electrode erosion but have low energy efficiency, about 40 % to 70 % (60 % to 90 % for arc torches) [73]. From this review, it clearly appears that the main plasma torch technology applied to waste gasification is the DC technology which is used in all the studies excepted in [32,85,90] In [66], one can notice that the H 2 and CO yields are strongly linked to the original composition of the waste treated and can vary, with the same experimental conditions, from 49.4 vol% to 64.4 vol% for H 2 and from 24.8 vol% to 36 vol% for CO in function of the nature of the waste. It is important to keep in mind that the H 2 and CO rates in the crude syngas is strongly linked to the oxidizing agent injected and/or the moisture content in the waste treated.…”
Section: Waste Gasification By Plasma Process At Lab Scalementioning
confidence: 97%
“…France [78], Czech Republic [71,[79][80][81][82][83][84] and Russia [85][86][87]. The product can be injected in solid form [71] or liquid [78], from a pyrolysis cycle or crushed.…”
Section: Plasma Torch Configurations In the Reactormentioning
confidence: 99%
See 2 more Smart Citations
“…Moustakas et al (2005; reported successful installation and testing of a demonstration 50 kg/h pilot plant with plasma vitrification system to treat industrial hazardous waste, as well as further performance optimization. Tendler et al (2005) presented a review and assessment of the hot temperature discharge physics and processing of the waste, including vitrification, gasification, power generation and environmental advantages. More recently, Hong et al (2006) and Bang et al (2006) developed microwave plasma torches to produce high temperature plasma flame.…”
Section: Introductionmentioning
confidence: 99%